Distance Learning Problems during the Covid-19 Pandemic - Amalia, Annisa Fitri; Purnamaningsih, Ine Rahayu (English Language Education, Universitas Internasional Batam, 2022)
The Covid-19 pandemic that occurred requires the government to take a stance to prevent the spread of the virus, including in the education sector. The online learning process during the Covid-19 pandemic had several problems. This research aims to find out the issues of Distance Learning or what is commonly referred to online during the Covid-19 pandemic and its solutions. Following the issues raised, this research data was obtained from various sources, such as journals, websites, and other sources. The results of this study indicate that there are multiple problems or problems experienced by students, namely, students become bored and less interested in participating in online learning activities because learning activities tend to be replaced with online assignments, students do not have learning support facilities, uneven internet network access sometimes tricky, high cost of internet quota, and not ready to implement the teaching and learning process remotely or online.